2007
DOI: 10.1016/j.bbrc.2007.05.057
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) mediates repression of TNF-α by decreasing levels of acetylated histone H3 and H4 at its promoter

Abstract: Prostaglandin metabolite 15-Deoxy-Δ 12,14 -prostaglandin J2 (15d-PGJ2) is known to inhibit a number of proinflammatory cytokines as well as being a ligand for nuclear receptor PPARγ. We investigated the ability of 15d-PGJ2 to inhibit TNF-α gene expression through mechanisms that involve histone modification. Pretreatment with 15d-PGJ2 at 10 μM inhibited LPS-stimulated TNF-α mRNA in THP-1 monocytes or PMA-differentiated cells to nearly basal levels. A specific PPARγ ligand, GW1929, failed to inhibit LPS-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For example, anti-inflammatory effects of PGD have now been recognized in leukocytes and other cells, especially after identification of its dehydrated metabolite, 15d-PGJ 2 [65]. 15d-PGJ 2 appeared to be more efficient in reducing the expression of TNF-α in THP-1 monocytes [66]. The observation that a high concentration of 15d-PGJ 2 inhibited the deposition of Aβ raised the question of whether high concentration of 15d-PGJ 2 can improve the cognitive decline of APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, anti-inflammatory effects of PGD have now been recognized in leukocytes and other cells, especially after identification of its dehydrated metabolite, 15d-PGJ 2 [65]. 15d-PGJ 2 appeared to be more efficient in reducing the expression of TNF-α in THP-1 monocytes [66]. The observation that a high concentration of 15d-PGJ 2 inhibited the deposition of Aβ raised the question of whether high concentration of 15d-PGJ 2 can improve the cognitive decline of APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…6). In this context, Engdahl et al [53] showed that THP-1 monocytes or PMA-differentiated cells treated with LPS increase histone H3 and H4 acetylation at the TNF-a promoter and that prostaglandin metabolite 15d-PGJ2 is able to block LPS-induced TNF-a expression by decreasing the acetylation level. They also showed that inhibition of HDAC with TSA, or overexpression of CBP, overcomes 15d-PGJ2-mediated repression of the TNF-a promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PPAR agonists inhibit the activation of genes associated with the inflammatory response, such as IL-2, IL-6, IL-8, TNF-α, and metalloproteases, by modulating signaling pathways involving nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB), activator protein 1 (AP-1), and signal transducer and activator of transcription proteins (STATs) [ 39 ]. The activation of PPARγ also mediates adipogenesis; studies have demonstrated that synthetic PPARγ ligands such as rosiglitazone [ 40 ] and natural ligands such as 15d-PGJ 2 [ 41 ] reduce serum levels and transcription of TNF-α.…”
Section: The Anti-inflammatory and Antioxidative Effects Of Ppar Agon...mentioning
confidence: 99%